Methicillin-resistant Staphylococcus aureus in Ohio EMS Providers: A Statewide Cross-sectional Study. (3rd March 2016) - Orellana, Robert C.; Hoet, Armando E.; Bell, Christopher; Kelley, Christina; Lu, Bo; Anderson, Sarah E.; Stevenson, Kurt B.
ABSTRACT: The objective was to determine the nasal carriage prevalence of methicillin-resistant Staphylococcus aureus (MRSA) among emergency medical service (EMS) personnel and the associated risk factors. A cross-sectional study was conducted among Ohio EMS personnel randomly sampled from 84 urban and rural agencies. Surveys assessing demographics, occupational history, health, cohabitation status, and hygiene practice were collected with nasal swabs from those who enrolled. Survey weight adjusted analysis was performed (1) to estimate MRSA nasal carriage prevalence of Ohio EMS providers, and (2) to identify variables associated with MRSA. MRSA was detected in 4.6% (13/280) EMS personnel sampled. After employing a survey-weighted analysis the following risk factors associated with MRSA carriage were identified: those who did not practice frequent hand hygiene after glove use (OR, 10.51; 95% CI, 2.54–43.45; P = 0.0012), living with someone with a recent staphylococcal infection (OR, 9.02; 95% CI, 1.03–78.98; P = 0.0470), and individuals with low frequency of hand washing (< 8 times per shift) (OR, 4.20; 95% CI 1.02–17.27; P = 0.0468). An additional risk factor identified through the logistic regression analysis on the study population was EMS workers with an open wound or skin infection (OR, 6.75; 95% CI, 1.25–36.36; P = 0.0262). However, this was not significant in the survey-weighted analysis. The high prevalence of MRSA in Ohio EMS personnel is both an occupational hazard and patient safety concern. Implementing methods to reinforce CDC guidelines for proper hygiene could decrease MRSA found in the EMS setting. Previous literature suggests that a reduction in MRSA colonization can lead to decreases in transmission and improved health for both patients and personnel.